Effect of homologous or heterologous vaccine booster over two initial doses of inactivated COVID-19 vaccine - Viravarn Luvira; Punnee Pitisuttithum (Taylor & Francis Group, 2024)
ABSTRACTIntroduction Inactivated vaccines were delivered to low- and middle-income countries during the early pandemics of COVID-19. Currently, more than 10 inactivated COVID-19 vaccines have been developed. Most inactivated vaccines contain an inactivated whole-cell index SARS-CoV-2 strain that is adjuvant. Whole virions inactivated with aluminum hydroxide vaccines were among the most commonly used. However, with the emerging of COVID-19 variants and waning of the immunity of two doses of after 3 months, WHO and many local governments have recommended the booster-dose program especially with heterologous platform vaccine.Area Covered This review was conducted through a literature search of the MEDLINE database to identify articles published from 2020 to 2023 covered the inactivated COVID-19 vaccines primary series with homologous and heterologous booster focusing on safety, immunogenicity, efficacy, and effectiveness.Expert opinion The inactivated vaccines, especially whole virion inactivated in aluminum hydroxide appeared to be safe and had good priming effects. Immune responses generated after one dose of heterologous boost were high and able to preventing severity of disease and symptomatic infection. A new approach to inactivated vaccine has been developed using inactivating recombinant vector virus-NDV-HXP-S vaccine.